Uso de las TAC para favorecer el proceso de enseñanza aprendizaje de los discentes de Pedagogía de las Ciencias Experimentales - Química y Biología - Narvaez Garay, Maryuri Stefany (2024)
Today, technology has transformed the way people live and learn. One of the main demands in Higher Education in Ecuador, the effective integration of Learning and Knowledge Technologies (LKT) represents a fundamental demand for educators. The objective of this study is to analyze the use of Learning and Knowledge Technologies (LKT) to favor the teaching-learning process of the students of the Experimental Sciences Pedagogy course - Chemistry and Biology, at the National University of Loja. The methodology presents a mixed approach, which involves the application of surveys to students, interviews to teachers and, in a complementary way, interviews to experts in educational technologies. The results show that ICTs act as facilitating tools, making learning more attractive and motivating; they also contribute to strengthen communication between teachers and students, with the objective of personalizing teaching. In conclusion, it is evident that LKT play an essential role in the educational context, contributing significantly to planning through the implementation of techniques and strategies that seek to optimize the pertinent and efficient use of educational technologies. Keywords: LKT, Technological tools; meaningful learning; professional training; digital competences; higher education.